Follicular dynamics and estradiol quantification during the estrous cycle of creole cows of the Blanco Orejinegro breed - Narváez Bedoya, Héctor Javier (2020)
The aim of this study was to characterize follicular dynamics and quantify oestradiol levels during an oestrous cycle in cows of the creole breed Blanco Orejinegro. Ten cows that were cycling were selected and underwent an oestrous synchronization protocol with the initial application of an intravaginal progesterone device (CIDR®) plus 2 mg of estradiol benzoate (day 0 - D0). On day D8 the device was removed and 150 µg of cloprostenol (Ciclase DL®) was inyected. In D9 1 mg of oestradiol benzoate was administered. After ovulation, ultrasound scans were performed every 24 hours, recording follicular dynamics and collecting blood for oestradiol quantification. The oestrous cycle duration was 21.0 ± 0.4 days, the diameter of the ovulatory follicle was 14.3 ± 0.5 mm and of the major subordinate follicle was 6.0 ± 0.5 mm, the growth rate of the dominant follicle during the 96 hours prior to ovulation was 1.05 ± 0.4 mm/day. In conclusion, the follicular dynamics and oestradiol levels of creole cows of the Blanco Orejinegro breed present similar patterns to those observed in Bos taurus and Bos indicus breeds.